The Role Of Green Insurance Products In Sustainable Economic Development - Yusufov Asfandiyor Eldor ugli (Periodica Journal, 2025)
This article analyzes the types of green insurance products, their share in the international market and their impact on sustainable economic development. Based on the analysis of literature and the experience of different countries, it is determined that green insurance is not only a means of financially eliminating environmental risks, but also an important factor in improving the investment environment and supporting the green economy. The state and factors of development of insurance markets in Europe, the USA and Asia are analyzed
Keywords: green insurance; sustainable development; environmental risks